Chromosomes and Cytogenetics of Trematodes (Global Journal of Medical Research, 2016)
Here we review the literature from 1902 to 2015 and the current status of knowledge of the chromosomes and cytogenetics within the family species of trematodes. Karyological data are discussed and tabulated for 278 species of trematodes. Numerous species of trematodes points towards the continued efforts in this field of research. The present study also revealed new data on chromosome complements of diplozoid parasites, namely Diplozoon Kashmirensis Kaw, 1950 from Schizothorax esocinus; Diplozoon aegyptensis Fischthal et Kuntz, 1963 from Schizothorax plagiostomum; Diplozoon guptai Fayaz and Chishti, 1999 from Schizothorax curvifrons and one digenean i.e., Clinostomum schizothoraxi Kaw, 1950 from S. curvifrons which included one metacentric (no. 1); two submetacentric (no.s 2 and 3); three subtelocentric (no.s 4; 5 and 6) and four acrocentric (no.s 7, 8; 9 and 10) chromosome pairs. All the three species of Diplozoon species are characterized by the same number of chromosomes i.e., 2n=14 in which D. kashmirensis is characterized by seven pairs of long (up to 14.13 μm) chromosomes and all chromosome pairs are acrocentric.
Keywords: diplozoon; schzothorax; karyotype; kashmir; metacentric; acrocentric; telocentric; subtelocentric